Metal (Co/Mo)–N bond anchor-doped N in porous carbon for electrochemical nitrogen reduction. Issue 6 (20th January 2021) - Liu, Yanyan; Zhang, Shengbo; Li, Wenyi; Zhou, Hongjian; Wang, Guozhong; Zhang, Haimin
Abstract : Co (Mo) atoms coordinated with N atoms on N-doped porous carbon could not only effectively inhibit the disaggregation of doped N atoms, but also provided abundant active sites, thus promoting the enhancement of the electrochemical NRR performance. Abstract : Currently, nitrogenous electrocatalysts (particularly, nitrogen (N)-doped carbon materials) have attracted extensive attention owing to their superior electrochemical nitrogen reduction reaction (NRR) performances. Unfortunately, doped nitrogen atoms could directly contribute to the formation of ammonia via dissociation and hydrogenation. Significantly, the type of N atoms (pyrrolic-N, pyridinic-N, or graphitic-N) in N-doped carbon donated to NH3 formation still needs to be verified. Here, using chitosan-derived N-doped porous carbon as an NRR electrocatalyst, we demonstrated that pyrrolic-N and pyridinic-N could disaggregate and hydrogenate to form NH3, leading to the increase in the yield of ammonia. To remedy this issue, metal–N bonds as an efficient and universal strategy were proposed to anchor doped N in porous carbon for NRR. Specifically, Co (Mo) atoms coordinated with N atoms could not only effectively inhibit the disaggregation of doped N atoms but also successfully promote the electrocatalytic NRR activity, thus yielding a boosted NRR performance.